Attitudes of Public Relations Practitioners in Jordanian Commercial Institutions Toward Commitment to Public Relations Ethics - Mazahreh, Manal Hilal (Dirasat: Human and Social Sciences, 2026)
Objectives: The study aims to identify the attitudes of public relations practitioners in Jordanian commercial institutions toward a commitment to public relations ethics. Methods: The study belongs to the field of descriptive studies، conducting a questionnaire survey to collect data from a sample of 100 public relations practitioners working in Jordanian commercial institutions. Results: The findings revealed that most Jordanian public relations practitioners possess awareness and knowledge of public relations ethics، with a percentage of 69%. Their attitudes toward these ethics were notably high، particularly in commitment to guidelines and regulations from senior management، with a mean score of 4.34. Commitment to religious principles emerged as a key factor influencing the ethics of public relations practitioners، with a high mean score of 3.94، followed by societal values and customs with a mean score of 3.78. Conversely، the respondents’ attitudes toward formalizing the ethics of public relations practice were moderate، with the highest being the establishment of a binding ethical framework and holding accountable those who violate these ethics، with equal average scores of 3.00. Conclusion: The study concluded that several factors influence the commitment of public relations practitioners to professional ethics، the most important of which are religion and societal values. The respondents emphasized the importance of regulating the ethics of public relations by establishing an ethical framework that practitioners must follow and holding accountable those who violate these ethics. The study recommended the need to set standards and rules for the ethics of public relations work by a specific authority to ensure that practitioners in Jordanian institutions adhere to them، in order to preserve the profession.